Association between sleep disorders and subsequent chronic spontaneous urticaria development: A population-based cohort study. Issue 34 (August 2018) - He, Guan-Yi; Tsai, Tsen-Fang; Lin, Cheng-Li; Shih, Hong-Mo; Hsu, Tai-Yi
Abstract : Abstract: Patients with chronic spontaneous urticaria (CSU) often have sleep disorders (SDs) because of pruritus. However, SDs might also contribute to the development of CSU. Here, we present the first population-based cohort study on the association between SDs and subsequent CSU development. This study investigated whether SDs increase the risk of CSU by using a population-based database in Taiwan. This retrospective matched-cohort study included 105, 892 patients with new-onset SDs (SD cohort) and 105, 892 randomly selected controls (control cohort). Each patient was monitored for 10 years to individually identify patients who were subsequently diagnosed as having CSU during the follow-up period. A Cox proportional hazard regression analysis was conducted to determine the risk of CSU in patients with SDs compared with the controls. All relevant comorbidities were more prevalent in the SD cohort than in the control cohort ( P  < .001). During the follow-up period, the incidence rates of CSU among the patients with SDs and controls were 53.4 and 28.3 per 10, 000 person-years, respectively. After adjustment for age, sex, and comorbidities, the adjusted hazard ratio for CSU in the SD cohort was 1.83 (95% confidence interval = 1.73–1.93, P  < .001). The risk of CSU was higher in the patients with SDs than in the controls.